Biomass Pyrolysis-Current status and future directions. Issue 19 (1st October 2016) - Kumar, Vinod; Nanda, Manisha
ABSTRACT: The declining reserves of fossil fuels and fossil fuel-related environmental issues, especially greenhouse gas (carbon dioxide, methane) emissions, have posed a great threat and challenge to the sustainability of the world economy, the global environment, and hence the quality of life of human beings. Biomass pyrolysis could help reduce both the world's dependence on oil and CO2 production. These bio-oils have the potential to cut CO2 emission because they are made up of plants that use CO2 for growth. There is a need to integrate process operation and reactor design to improve the effectiveness of different processes used for biomass to produce multiple products using a combination of technologies.